Wealth, poverty, and charity in Jewish antiquity - Gardner, Gregg (The S. Mark Taper Foundation imprint in Jewish studies, 2022)
Introduction -- The wealth of the early rabbis -- Harvest allocations for the poor -- Charity laws -- Giving mammon (wealth) -- Pay for the giver -- Charity as an investment -- Poverty relief and the anxiety of wealth -- Conclusion.